2015
DOI: 10.1007/s40800-015-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

Mood, Personality, and Behavior Changes During Treatment with Statins: A Case Series

Abstract: Psychiatric adverse drug reactions (ADRs) have been reported with statin use, but the literature regarding statin-associated mood/behavioral changes remains limited. We sought to elicit information germane to natural history and characteristics of central nervous system/behavioral changes in apparent connection with statin and/or cholesterol-lowering drug use, and delineate mechanisms that may bear on an association. Participants (and/or proxies) self-referred with behavioral and/or mood changes in apparent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 85 publications
1
33
1
1
Order By: Relevance
“…Clinically, the use of PCSK9 inhibitors has raised questions about neurocognitive side effects (Koren et al., ; Walker, ), although this is controversial as recent data do not support major effects on cognitive function (Giugliano et al., ). Furthermore, a recent study suggested a possible link between PCSK9 inhibitors and depression (Alghamdi et al., ), which is in line with long‐standing concerns about lipid‐lowering drugs and their association with depression (Cham et al., ; Hyyppa et al., ; Lohoff, ; Morales et al., ).…”
mentioning
confidence: 60%
“…Clinically, the use of PCSK9 inhibitors has raised questions about neurocognitive side effects (Koren et al., ; Walker, ), although this is controversial as recent data do not support major effects on cognitive function (Giugliano et al., ). Furthermore, a recent study suggested a possible link between PCSK9 inhibitors and depression (Alghamdi et al., ), which is in line with long‐standing concerns about lipid‐lowering drugs and their association with depression (Cham et al., ; Hyyppa et al., ; Lohoff, ; Morales et al., ).…”
mentioning
confidence: 60%
“…Post-marketing surveillance has continued to uncover case reports of cognitive effects associated with statin use since the FDA report. A case series aimed to describe the potential behavioral and psychiatric changes in statin users and found most of the adverse reports met presumptive criteria for “probable” or “definite” causality by the Naranjo score [ 20 ]. Consistent with previous reports, lipophilic statins (atorvastatin, simvastatin, and lovastatin) were identified as the most commonly associated with cognitive impairment ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most prescribed medications for hyperlipidemia in diabetes include Fibrates and Stains. However, side effects of Fibrates and Stains [7][8][9] makes it significant to develop functional foods-and natural products-based treatments which could be safer and more tolerable for patients.…”
Section: Introductionmentioning
confidence: 99%